Relative Age and Depositional Environment of The Limestone Unit of Karangsambung Formation in Jatibungkus Hill, Kebumen Geopark, Indonesia - Kurniasih, Anis; Wicitra, Annisa Puspa; Qadaryati, Nurakhmi; Khorniawan, Wahyu Budhi; Dalimunthe, Hasnan Luthfi; Setyawan, Reddy; Jayanti, Anita Galih Ringga (UIR PRESS, 2026)
The Jatibungkus Hill is an isolated karst hill and is one of the olistolith fragments in the Karangsambung Formation deposited as olistostrome deposits. This formation formed above the Luk-Ulo Mélange Complex, one of the geological heritage sites in the Kebumen Geopark. The presence of limestone as a fragment in the olistostrome deposits requires further investigation because its formation history is related to regional geological history. This study aims to determine the relative age and depositional environment of limestone in Jatibungkus Hill based on microfossil analysis through petrographic observations. Of the 39 rock samples obtained during field data collection, 15 rock samples were selected for petrographic analysis. The petrographic analysis is divided into two parts, namely descriptive methods and point counting as the basis for classifying carbonate rocks. Based on the classification results, reef facies analysis was conducted using facies zonation and standard microfacies (SMF) to obtain an overview of the limestone depositional environment. In addition, the types of large foraminifera fossils and algae were also used as a basis for determining the relative age. The lithology found in the research area consist of packstone, rudstone, grainstone, and crystalline limestone. The limestone depositional environment is located in SMF 4, SMF 5, and SMF 6 which are included into FZ 4 (Slope) on a restricted carbonate platform. This facies zone influenced by currents and waves between the storm base wave and the normal base wave. The petrographic analysis showing the domination of large bioclastic grain indicating that the deposition were under a high energy. The influence of waves is also reflected in the mixture of bioclass and lithoclast grains or high-density terrigenous clastics that are observed in most of the samples. This facies contains more quartz clastics and bioclast grains than carbonate mud as consistently observed in the identified samples.The association of large benthic foraminifera fossils and algae indicates that the limestone was formed in Zone Ta1 (Late Paleocene) characterized by the presence of Discocyclina sp., Ranikothalia sp., Nummulites sp., Miscelanea sp., Distichoplax biserialis, and Parachaetes sp. It can be seen that the deposition of the limestone olistolith occured after the initial subduction event which produced the mélange complex in Early Cretaceous.